Spontaneous bacterial peritonitis and pneumonia caused by Bordetella bronchiseptica - Nomonde Ritta Dlamini; Ahmed Bhamjee; Penelope Levick; Evelyn Uniacke; Husna Ismail; Anthony Smith (Journal of Infection in Developing Countries)
Bordetella bronchiseptica is a rare cause of invasive human infection. The most common infection in humans is the respiratory tract infection and it is usually associated with immunosuppression, particularly acquired immunodeficiency syndrome (AIDS). We report a case of a pneumonia and peritonitis in a 42-year-old female with alcoholic liver disease. The patient died despite treatment with antibiotics. This case illustrates the potential virulence of B. bronchiseptica in susceptible patients and to our knowledge it is the first case of primary peritonitis due to this organism.